Analysis of the risks and preventions of cubing forest species in the Eastern Brazilian Amazon (Research, Society and Development, 2023)
In this work, a study was carried out on the risks associated with the activity of logging logs and forest residues in the forests of the State of Pará, seeking to identify the risks of accidents at work and their prevention that can be listed on this activity through bibliographical consultation. and work activities. As a result, the following factors for the prevention of accidents at work were obtained: control measures, obeying the correct time of activities and the use of Individual Protection Equipment - EPI and Collective Protection Equipment - EPC.